Implementasi Balanced Scorecard Sebagai Alat Pengukur Kinerja pada PT. Noor Thoibah Banjarbaru - yudi rahman lisda ramadhani (Jurnal Ilmiah Ekonomi Bisnis, 2020)
ABSTRACT Implementation of the Balanced Scorecard as a Measuring Tool Performance at PT. Noor Thoibah Banjarbaru Yudi Rahman The purpose of this study is to provide input in terms of measuring the correct and relevant Balanced Scorecard based on the theory and standards of financial accounting which are a form of business accountability and company management performance. In this study the method used is the Balanced Scorecard. The Balanced Scorecard measures the company's performance from: 1. Growth and Learning Perspective, 2. Internal business process perspective, 3. Customer perspective, and 4. Financial perspective. The author analyzes PT Noor Thoibah Banjarbaru using data from 2017-2018 to analyze financial perspectives, while for other perspectives the writer analyzes through questionnaire calculations distributed to PT Noor Thoibah Banjarbaru staff and customers. From the results of the analysis conducted by the author, it is known that the performance of PT Noor Thoibah Banjarbaru as a whole is quite good. And of course with the use of the Balanced Scorecard Method will get accurate performance measurement results so it is very important for the management of PT. Noor Thoibah Banjarbaru both in the process of planning, decision making, and controlling, as well as in realizing the company's overall vision and mission.